1984
DOI: 10.1177/039139888400700409
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Disturbances in Experimental Hepatic Coma Rats

Abstract: In our previous paper (1), we discussed the in-vitro adsorption spectrum of plasma amino acids by coated charcoal hemoperfusion. We now describe the general amino acid disturbances in plasma, CSF and cerebrum in the galactosamine induced hepatic coma model in rats. All aromatic amino acids (AAA) increased significantly in the three compartments studied. Branched chain amino acids (BCAA) were either elevated to a much lesser extent or remained unchanged. The molar ratio of BCAA:AAA was consequently reduced. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Intracranial hypertension was an important finding in our study, although no evidence of edema was observed on gross or microscopic examination of the brain in the study of Diaz-Buxo et al 44 A higher dose of 1.7-2.0 g/kg of D-galactosamine may be needed in the dog for the formation of cerebral edema. The development of cerebral edema and intracranial hypertension after infusion of D-galactosamine is supported by past reports using rats 36,45,46 and rabbits. 47,48 Although the current study was conducted in an experimental facility at 9.4 T, observations made in this study regarding brain lactate are transferable to the clinical setting.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Intracranial hypertension was an important finding in our study, although no evidence of edema was observed on gross or microscopic examination of the brain in the study of Diaz-Buxo et al 44 A higher dose of 1.7-2.0 g/kg of D-galactosamine may be needed in the dog for the formation of cerebral edema. The development of cerebral edema and intracranial hypertension after infusion of D-galactosamine is supported by past reports using rats 36,45,46 and rabbits. 47,48 Although the current study was conducted in an experimental facility at 9.4 T, observations made in this study regarding brain lactate are transferable to the clinical setting.…”
Section: Discussionsupporting
confidence: 59%
“…supported by past reports using rats 36,45,46 and rabbits. 47,48 Although the current study was conducted in an experimental facility at 9.4 T, observations made in this study regarding brain lactate are transferable to the clinical setting.…”
Section: Brain Lactate By Mrssupporting
confidence: 62%
“…ALF causes marked, but nonspecific hyperaminoacidemia (41)(42)(43)(44)(45), attributed to hepatocellular damage with leakage of intracellular amino acids into the circulation (41). In most patients, this hyperaminoacidemia involves either those amino acids with high intracellular concentrations (glutamine, glutamate, alanine, glycine, lysine, threonine, and histidine) or those metabolized predominantly in the liver (phenylalanine, tyrosine, and methionine) (41).…”
Section: Discussionmentioning
confidence: 99%